Pola Hidup Sehat Atlet Bola Voli: Studi Survei di Masa Pandemi Covid-19 - M. Raihan Gumilang; Mela Aryani; Adi Rahadian; Edi Setiawan; Zsolt Németh (Ilmu Olahraga, 2022)
The purpose of this study was to conduct a survey of healthy lifestyles for volleyball athletes during the COVID-19 pandemic crisis. In this study using a descriptive survey method. The research subjects came from volleyball athletes from one area in Cianjur Regency (n = 25) with female (n = 10) and male (n = 15) gender characteristics, ages from 20-30 years, weight 55-70 kg and height 165-175 cm. The instrument used to measure a healthy lifestyle refers to eating patterns, activity patterns, hygiene patterns and resting patterns. Data analysis using Ms. Excel 2010 to find mean, frequency and percentage values. The first findings of this study indicate that the athlete's diet has an average percentage of 69.33 which is included in the moderate criteria, the second finding shows that the activity pattern has an average percentage of 73.33 which is included in the moderate criteria, the third finding shows that the average hygiene pattern the average percentage is 81.33 which is included in the high criteria and the latest findings show that the average rest pattern is 77.33 which is included in the good criteria. Thus, it can be concluded that volleyball athletes in Cianjur Regency still maintain a healthy and regular lifestyle even during the COVID-19 pandemic